2020
DOI: 10.5194/essd-12-577-2020
|View full text |Cite
|
Sign up to set email alerts
|

The dead line for oil and gas and implication for fossil resource prediction

Abstract: Abstract. Fossil fuel resources are invaluable to economic growth and social development. Understanding the formation and distribution of fossil fuel resources is critical for the search and exploration of them. Until now, the vertical distribution depth of fossil fuel resources has not been confirmed due to different understandings of their origins and the substantial variation in reservoir depths from basin to basin. Geological and geochemical data of 13 634 source rock samples from 1286 exploration wells in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(6 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…According to the active source rock depth limit (Pang et al, 2020), the basin's heat flow generally controls the maximum burial depth for source rocks to generate and expel hydrocarbons produced by thermal cracking of kerogen (Behar et al, 1997). Since 1.6 MaBP, the Beaufort MD Basin exhibits an approximate heat flow of 55 mW m -2 (Figure 5B) in agreement with the moderate-heat-flow (40-60 mW m -2 ) basin suggested by Pang et al (2020).…”
Section: Numerical Model Geometry and Parametrizationsupporting
confidence: 53%
See 1 more Smart Citation
“…According to the active source rock depth limit (Pang et al, 2020), the basin's heat flow generally controls the maximum burial depth for source rocks to generate and expel hydrocarbons produced by thermal cracking of kerogen (Behar et al, 1997). Since 1.6 MaBP, the Beaufort MD Basin exhibits an approximate heat flow of 55 mW m -2 (Figure 5B) in agreement with the moderate-heat-flow (40-60 mW m -2 ) basin suggested by Pang et al (2020).…”
Section: Numerical Model Geometry and Parametrizationsupporting
confidence: 53%
“…According to the active source rock depth limit (Pang et al, 2020), the basin's heat flow generally controls the maximum burial depth for source rocks to generate and expel hydrocarbons produced by thermal cracking of kerogen (Behar et al, 1997). Since 1.6 MaBP, the Beaufort MD Basin exhibits an approximate heat flow of 55 mW m -2 (Figure 5B) in agreement with the moderate-heat-flow (40-60 mW m -2 ) basin suggested by Pang et al (2020). It implies that the upper limit of hydrocarbon generation, migration and accumulation is below 2,500 mbgl, conforming to the assumption that the GH-forming thermogenic gases originated from the Taglu Sequence (Figure 2B).…”
Section: Numerical Model Geometry and Parametrizationmentioning
confidence: 99%
“…During deep burial, δ 13 C org values of kerogen may increase by up to +1‰ due to generation of 13 C-depleted oil and gas (Clayton, 1991). The present kerogen maturity (R o ) of the lower Cambrian black shales from the Tadong2 Well is about 2.7% (Zhang et al, 2004), higher than the 'oil window' (R o : 0.7-1.3%), but still in the 'gas window' (R o : <3.5%) (Pang et al, 2020). As such, the present δ 13 C org values should be slightly heavier than those of the primary δ 13 C org values.…”
Section: Reliability Of Carbon Isotope Valuesmentioning
confidence: 99%
“…The Mallik NGH accumulation occurs below thick permafrost and overlays directly on a free gas field sourced from deep thermal genetic gas of the basin. A basin wide study in the Beaufort-Mackenzie Basin (BMB) based on petrophysical logs from 251 oil and gas exploration wells showed that, although the NGH occurs in 122 wells (50%), only 7 contain net thickness greater than 5 meters, accounting for < 3% of the total wells studied (Osadetz and Chen 2010).…”
Section: Volumetric Methods Principlementioning
confidence: 99%